2012
DOI: 10.1258/ar.2012.120314
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization of spinal tumors: variables affecting intraoperative blood loss after embolization

Abstract: Embolization technique or completeness has a limited effect on operative blood loss after preoperative spinal tumor embolization. Operative blood loss from spinal surgery is dependent primarily on the invasiveness of the surgery. Although preoperative embolization is a relatively safe procedure, there remains a risk of cord ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 20 publications
3
46
0
Order By: Relevance
“…This is in concordance with previous studies where no major complications were reported [11,3032] . Our results showed significantly less blood in a variety of surgically resected bone tumours as compared with the preembolisation era, and comparable blood loss to other studies [12,27,29] . In a study done by Thiex et al [29] on 104 spinal tumors, the blood loss was found to be in the range of 20015000 mL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is in concordance with previous studies where no major complications were reported [11,3032] . Our results showed significantly less blood in a variety of surgically resected bone tumours as compared with the preembolisation era, and comparable blood loss to other studies [12,27,29] . In a study done by Thiex et al [29] on 104 spinal tumors, the blood loss was found to be in the range of 20015000 mL.…”
Section: Discussionsupporting
confidence: 88%
“…Out of 6 patients they studied, three patients had GCT and 3 patients had ABC. There are scattered case reports, describing the role of TAE in limbgirdle location where GCT and ABCs were the common histology [25,26,27] . Barton et al [24] also reported that, surgery occurred within 3 d of embolization, blood loss was 5001500 mL, comparing to 15002800 mL at 414 d post embo lisation, due to recanalization and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate analysis only showed the extent of the surgical procedure to be the only significant factor, while tumor characteristics such as the vascularity, histology, and particulars of embolization to be not statistically significant. [22] Robial and colleagues, in a retrospective review of microsphere preoperative embolization for metastatic tumor, found no difference in blood loss regardless of embolization.…”
Section: Discussionmentioning
confidence: 98%
“…While a number of aforementioned papers demonstrate the safety and benefit of decreased intraoperative blood loss with the use of preoperative embolization, a recently published univariate analysis of sixty-two patients with prior preoperative embolization and tumor resection did not find tumor vascularity as a significant factor affecting blood loss. [22] Kobayashi and colleagues found the tumor volume, the invasiveness of the planned procedure, as well as the approach to be significant factors. Multivariate analysis only showed the extent of the surgical procedure to be the only significant factor, while tumor characteristics such as the vascularity, histology, and particulars of embolization to be not statistically significant.…”
Section: Discussionmentioning
confidence: 99%